ЖАНРОВЫЕ ОСОБЕННОСТИ ПУБЛИЦИСТИКИ ПИСАТЕЛЯ - Абдимуратов, А. (SCIENCE and SOCIETY, 2024)
The article presents considerations on the uniqueness of the genres of the writer's journalism. It also takes into account the theoretical views of foreign scientists on the theory of journalism genres. The types of synthesis of genre forms as a distinctive feature of publication in the work of the writer T. Kaipbergenov are discussed.
Keywords: literary journalism; genres of journalism; creativity of T. Kaipbergenov; artistic tradition; expression; meaning; skill